The Effect Of Internal Audit And Accounting Information Systems On Internal Control - Julianti, Mira; Hudi, Ilham (Balance Vocation Accounting Journal, 2025)
TThe effectiveness of internal controls is a critical aspect in the hospitality industry to ensure accountability and operational efficiency. This study aims to analyze the influence of internal audit and accounting information system on internal control at Fox Hotel Pekanbaru. The quantitative research method was applied with purposive sampling techniques on 41 respondents consisting of front office and back office employees. Primary data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 25. The results showed that internal audits and accounting information systems significantly affected internal control with a contribution of 57.4%. These findings make a practical contribution to hotel management in strengthening the internal control structure through the optimization of audit functions and information systems. The novelty of this research lies in the specific approach to the hotel industry in the Pekanbaru area that has not been studied before, as well as the simultaneous testing of two key variables in building an effective internal control system